Adverse events associated with ustekinumab in Crohn's disease treatment: an analysis based on the FAERS database - Guo, Chiwei; Zhao, Shujuan (Frontiers in Medicine, 2025)
BackgroundUstekinumab, approved in 2016 for the treatment of Crohn's disease (CD), its safety profile remains insufficiently characterized in real-world settings. This study aims to enhance clinical safety by identifying adverse events (AEs) associated with ustekinumab through data mining of the U.S. Food and Drug Administration Adverse Event Reporting System (FAERS) database.MethodsAEs data for ustekinumab in CD treatment were extracted from the FAERS database. Duplicate and incomplete reports were excluded during preprocessing. Signal detection was performed using the reported odds ratio (ROR), proportional reporting ratio (PRR), Bayesian confidence propagation neural network (BCPNN), and empirical Bayesian geometric mean (EBGM), with established thresholds applied for signal identification. AEs were classified based on the system organclass (SOC).ResultsA total of 17,187 AEs associated with ustekinumab in CD were identified, generating 44,232 signals across 24 SOCs and 258 preferred terms (PTs). The most frequent reports were categorized under “injury, poisoning, and procedural complications,” while “infections and infestations” emerged as one of the most frequently reported SOCs. Statistically significant PTs included abscess (ROR = 25.36, 95% CI: 22.51–28.58), clostridium difficile infection (ROR = 14.37, 95% CI: 12.72–16.24), and lower respiratory tract infection (ROR = 13.54, 95% CI: 12.37–14.83). Notable signals were also identified for hepatobiliary disorders (2.24% mortality) and cardiac disorders (7.50% mortality, the highest among all SOCs). Rare events, such as congenital pulmonary airway malformation, were observed; however, these findings were limited to a small number of cases and warrant cautious interpretation.ConclusionIn the treatment of CD with ustekinumab, it is critical to monitor not only common AEs like infections and tumors, but also less frequent yet severe AEs, including cardiac disorders, hepatobiliary disorders, and possible congenital anomalies. The latter, however, requires further validation through additional clinical evidence.